Linux web operations LiveLessons (sneak peek video training) - Whaley, Ben.; Safari eBooks ([S.l.] : Addison-Wesley Professional, 2014)
"Operating the systems that run the web is complex and specialized. New users have much to learn, and developers are commonly more interested in writing code than configuring systems. Even a competent Linux administrator from another industry needs new skills to be successful working on the web. Automation and orchestration is increasingly prevalent on systems powering the web, and these technologies require new skills for administrators. In Linux Web Operations LiveLessons, Ben Whaley covers the architecture underlying a modern web stack. Centered around a simple example Python web application, the content focuses on general concepts that apply to all applications, then provides a deep dive into specific examples to drive concepts home. The content covers setting up web, application, and database servers for a web application; configuring master/slave DNS; using Ansible configuration management to automate deployment; working with APIs; running applications using Docker containers; and working with cryptography software."--Resource description page.
Title from resource description page (viewed June 26, 2014).
Presenter, Ben Whaley.
Keywords: Linux; Web site development; Internet programming; Electronic books